Cisco Systems : launching the ASR 1000 series router using social media marketing - Sawhney, Mohanbir S. (London : SAGE Publications Ltd, 2017)
This case focuses on Cisco Systems innovative probe-and-learn approach to using social media to launch its ASR 1000 Series Edge Router. The company had decided to eschew traditional print and TV media in marketing the new product and had decided instead to focus its efforts entirely on digital marketing and social media to attract the attention of its target market. The case discusses Ciscos bold plan to launch the ASR 1000 Series "virtually, visually, and virally" and the digital tactics employed by the Cisco Systems marketing team to accomplish this ambitious goal. Business marketers normally adopt a more serious and traditional approach to marketing its products but in this case Cisco had decided to buck that trend by exploring digital tools and social gaming avenues which its target clientthe technical communitywere increasingly frequenting. Ciscos challenge lay in whether this new approach and resultant value proposition would resonate with its technical audience and give the ASR 1000 Router the kind of publicity it needed to have. The case is set at a time when social media was burgeoning as a promising way to engage consumers more deeply with brands and products, but marketers were still experimenting with the tools and tactics of social media for marketing.
Originally published: Sawhney, M. (2011). Cisco Systems: Launching the ASR 1000 series router using social media marketing. 5-111-008 Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; Cisco Systems, Inc; electronic books; Internet industry -- United States; Internetworking (Telecommunication) -- United States; Business enterprises -- Computer networks -- United States